3D Printing for veterinary anatomy: An overview. (8th November 2019) - Wilhite, Ray; Wölfel, Inga
Abstract: Many applications for 3D printing have appeared in the field of veterinary medicine, including many opportunities to use 3D‐printed models in anatomical teaching. Here, we present background information on the basic types of 3D printers as well as the advantages and disadvantages of each type. We discuss methods for obtaining 3D models which can range from downloading of models to primary collection of data from CT and MRI data sets or even generating models using 3D modelling software. We review the various types of software needed to both process 3D data as well as software needed to prepare the 3D models for printing. The size and complexity of the desired model will dictate the type(s) of printer(s) which can be used. Cost, print resolution desired and cleanup time for prints are also key factors to consider when choosing a 3D printer. Here, we presented four specific examples of how 3D prints can be used for teaching veterinary gross anatomy. Examples using fused deposition modelling, stereolithography and colourjet printing printers are given to show the wide range of anatomical models that can be made using the various 3D printing techniques.